COLLABORATION MANAGEMENT STRATEGIES IN IMPROVING THE PERFORMANCE OF MSMEs AT MAWARIDUSSALAM MICRO WAQF BANK - Toni Hidayat; Ratna Sari Dewi; Yayuk Yuliana; Indra Fauzi; Muhammad Radiansyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study employs a descriptive qualitative research method. The qualitative data were analyzed using NVivo 12 software. On the MSME collaboration side, the analysis results indicate several important indicators that support the success of collaboration management, namely goal alignment, knowledge sharing, long-term commitment, effective communication, risk and reward sharing, as well as trust and transparency. Goal alignment serves as the foundation for establishing focused cooperation among MSME actors and supporting institutions. In addition, knowledge sharing helps MSME actors gain new insights related to business development, management, and marketing strategies. Long-term commitment and effective communication are essential factors in maintaining sustainable collaboration, ensuring that cooperative relationships function optimally. Furthermore, trust, transparency, and fair distribution of risks and benefits strengthen relationships among stakeholders involved in MSME development. Regarding MSME performance, the mind map analysis shows that performance improvement can be observed through several indicators, including profit growth, capital growth, market or marketing growth, sales growth, and workforce growth. Keywords: Collaboration Management, Performance, MSMEs.